Plant-Derived Polysaccharides Regulated Immune Status, Gut Health and Microbiota of Broilers: A Review - Zhang, Bolin; Liu, Ning; Hao, Meilin; Zhou, Jianhong; Xie, Yuxiao; He, Zhen (Frontiers in Veterinary Science, 2022)
In modern intensive breeding system, broilers are exposed to various challenges, such as diet changes and pathological environment, which may cause the increase in the incidence rate and even death. It is necessary to take measures to prevent diseases and maintain optimal health and productivity of broilers. With the forbidden use of antibiotics in animal feed, polysaccharides from plants have attracted much attention owing to their lower toxicity, lower drug resistance, fewer side effects, and broad-spectrum antibacterial activity. It had been demonstrated that polysaccharides derived from plant exerted various functions, such as growth promotion, anti-inflammation, maintaining the integrity of intestinal mucosa, and regulation of intestinal microbiota. Therefore, the current review aimed to provide an overview of the recent advances in the impacts of plant-derived polysaccharides on anti-inflammation, gut health, and intestinal microbiota community of broilers in order to provide a reference for further study on maintaining the integrity of intestinal structure and function, and the related mechanism involved in the polysaccharide administration intervention.